TMS over the supramarginal gyrus delays selection of appropriate grasp orientation during reaching and grasping tools for use - McDowell, Tomás; Holmes, Nicholas P.; Sunderland, Alan; Schürmann, Martin (Elsevier, 2018)
Tool use, a ubiquitous part of human behaviour, requires manipulation control and knowledge of tool purpose. Neuroimaging and neuropsychological research posit that these two processes are supported by separate brain regions, ventral premotor and inferior parietal for manipulation control, and posterior middle temporal cortex for tool knowledge, lateralised to the left hemisphere. Action plans for tool use need to integrate these two separate processes, which is likely supported by the left supramarginal gyrus (SMG). However, whether this integration occurs during action execution is not known. To clarify the role of the SMG we conducted two experiments in which healthy participants reached to grasp everyday tools with the explicit instruction to use them directly following their grasp. To study the integration of manipulation control and tool knowledge within a narrow time window we mechanically perturbed the orientation of the tool to force participants to correct grasp orientation 'on-line' during the reaching movement. In experiment 1, twenty healthy participants reached with their left hand to grasp a tool. Double-pulse transcranial magnetic stimulation (TMS) was applied, in different blocks over left or right SMG at the onset of perturbation. Kinematic data revealed delayed and erroneous online correction after TMS over left and right SMG. In Experiment 2 twelve participants reached, in different blocks, with their left or right hand and TMS was applied over SMG ipsilateral to the reaching hand. A similar effect on correction was observed for ipsilateral stimulation when reaching with the left and right hands, and no effect of or interaction with hemisphere was observed. Our findings implicate a bilateral role of the SMG in correcting movements and selection of appropriate grasp orientation during reaching to grasp tools for use.